Oxidized nicandra physaloides polysaccharide-carboxymethyl chitosan composite hydrogel as well as preparation method and application thereof
The composite hydrogel is prepared by oxidizing the pseudoic acid slurry polysaccharide polysaccharide by reacting with carboxymethyl chitosan through Schiff base, which solves the problem of unstable structural and poor mechanical properties of the pseudoic acid slurry polysaccharide during gel formation, and achieves rapid gum formation and excellent mechanical properties of the hydrogel, which is suitable for wound dressings.
Patent Information
- Application Number
- CN202411736537.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-03-04
AI Technical Summary
The existing pseudo acid slurry polysaccharides have unstable structure during gel formation, poor mechanical properties, and uncontrollable glue formation time, making it difficult to prepare hydrogel wound dressings that can quickly gel formation.
By oxidizing pseudo acid slurry polysaccharides by sodium periodate, the two adjacent hydroxyl groups in its structure are converted into aldehyde groups, and the composite polysaccharide reversible covalent crosslinked hydrogel is prepared by reacting with carboxymethyl chitosan through Schiff base to control the molar ratio of pseudo acid slurry polysaccharides to sodium periodate and the mass ratio of oxidizing pseudo acid slurry polysaccharides to carboxymethyl chitosan.
The prepared oxidized pseudoacid slurry polysaccharide-carboxymethyl chitosan composite hydrogel has excellent mechanical properties, structural stability and rapid gel formation characteristics. It is suitable for wound dressings and is not cytotoxic.
Smart Images

Figure CN119552385A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of hydrogel material development, and specifically relates to an injectable, self-healing oxidized Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel and a preparation method and application thereof. Background Art
[0002] Hydrogel is an important soft material with a three-dimensional structure and high water content. Its structure contains a large number of hydrophilic groups such as carboxyl (-COOH) and hydroxyl (-OH). Therefore, it has good water absorption and biodegradability, which helps to provide a moist environment for the wound and promote wound healing.
[0003] Natural polysaccharides, such as cellulose, chitosan, sodium alginate, hyaluronic acid, pectin, etc., are ideal materials for preparing polysaccharide hydrogels because of their safety, non-toxicity, excellent biocompatibility, natural degradability, easy recognition by cell surface receptors, macromolecular properties that are conducive to cell adhesion and diffusion, and wide sources. However, although hydrogels prepared from single polysaccharides have a certain gelling effect, they have poor mechanical properties, low structural stability, and unsatisfactory adhesion effects, which are greatly limited in practical applications.
[0004] Since natural polysaccharides have a simple structure and are easy to modify, it is an effective strategy to modify polysaccharides and then prepare composite hydrogels through chemical cross-linking with other polysaccharides, thereby improving the mechanical properties, structural stability and adhesion of single polysaccharide hydrogels and giving the composite hydrogels new functional properties.
[0005] The design and preparation of self-healing hydrogels with dynamic covalent bonds is a current research hotspot. The Schiff base reaction is a chemical reaction that forms dynamic covalent imine bonds by cross-linking amino and aldehyde groups. It can react reversibly under mild conditions, allowing the hydrogel to restore its structure and function after damage. Hydrogels prepared based on the Schiff base reaction have many advantages, such as injectability, self-healing, in situ formation and good biocompatibility, and have been widely used in wound healing, drug delivery, tissue regeneration, tissue adhesion and other fields.
[0006] The seeds of Physalis alkekengi contain a rich layer of polysaccharides in the endosperm. The structure of this polysaccharide is mainly composed of galacturonic acid, which has the typical structural characteristics of low-methoxy pectin. It is usually made into "ice powder" for consumption by the people, and has high biological safety. However, the gels or microspheres developed with Physalis alkekengi are extremely limited. This is because the Physalis alkekengi polysaccharide is prone to structural instability and low mechanical strength when it is gelled with other polysaccharides. At the same time, it is difficult to control the cytotoxicity caused by excessive oxidation after oxidation. Therefore, there are few precedents for successfully preparing composite hydrogels with Physalis alkekengi.
[0007] Patent document CN 110721163 B discloses a method for preparing Pseudo-Physalis syringae gum microspheres, which comprises adding sodium alginate to an activator for activation, then adding aminothiol in a protective atmosphere to obtain a precursor solution, and then cross-linking with Pseudo-Physalis syringae polysaccharide and calcium salt to form a gel. The method has a complicated operation process, and the addition of activators and aminothiol is prone to biological toxicity, and the gelling time is long and uncontrollable, and cannot be used for rapid treatment of wounds.
[0008] Therefore, how to prepare a composite hydrogel by combining Physalis polysaccharide with other natural ingredients so that its gelation time is controllable, the gelation speed is fast, the structure is stable, the mechanical properties are excellent, and it can be well suited for wound dressings has become a technical problem that needs to be solved urgently. Summary of the invention
[0009] The present invention is to solve the above technical problems, thereby providing an injectable, self-healing oxidized Physalis polysaccharide-carboxymethyl chitosan composite hydrogel and its preparation method and application. The technical purpose of the present invention is to solve the problems that the existing Physalis polysaccharide is structurally unstable during gelation, has poor mechanical properties, and has uncontrollable gelation time, making it difficult to prepare a hydrogel wound dressing that can gel quickly.
[0010] In order to achieve the above object, the technical solution adopted by the present invention is as follows:
[0011] The present invention first provides a method for preparing an oxidized Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel, comprising the following steps:
[0012] (1) Extraction of Physalis polysaccharide: Dry the seeds of Physalis to obtain dry seeds, soak them in deionized water to swell them, stir and filter to collect the solution, perform rotary evaporation, then add ethanol to precipitate polysaccharides at 4°C, collect the polysaccharide precipitate, and freeze-dry to obtain Physalis polysaccharide;
[0013] (2) Oxidation of Physalis polysaccharide: dissolve Physalis polysaccharide in water, stir at 55°C to fully dissolve it, and then mix it with sodium periodate, wherein the molar ratio of the Physalis polysaccharide to sodium periodate is 5:1, and react at room temperature in the dark for 0.5 h. Add ethylene glycol in an amount equivalent to sodium periodate and continue stirring for 30 min to terminate the reaction. The reaction mixture is dialyzed. After the dialysis is completed, the obtained product is pre-frozen and then freeze-dried in a vacuum freeze dryer to obtain oxidized Physalis polysaccharide, which is prepared into a solution.
[0014] (3) preparing a carboxymethyl chitosan solution: weighing carboxymethyl chitosan and dissolving it in deionized water to prepare a carboxymethyl chitosan solution with a concentration of 1 wt %;
[0015] (4) Preparation of oxidized Physalis polysaccharide-carboxymethyl chitosan composite hydrogel: oxidized Physalis polysaccharide solution and carboxymethyl chitosan solution were mixed in a mass ratio of 1:2, and vortexed in a vortexer for 10 seconds to obtain oxidized Physalis polysaccharide-carboxymethyl chitosan composite hydrogel.
[0016] The inventors use the Schiff base reaction mechanism, and choose to convert two adjacent hydroxyl groups in the structure of the pseudo-Physalis polysaccharide into aldehyde groups after sodium periodate oxidation, thereby preparing a composite polysaccharide reversible covalent cross-linked hydrogel by Schiff base reaction with the amino group in the carboxymethyl chitosan structure. However, since the structure of the pseudo-Physalis polysaccharide is unstable after gelation, the mechanical properties are poor, and the problem of cytotoxicity is prone to occur after oxidation, the inventors have conducted a lot of exploratory research and finally determined the above-mentioned dosage ratio. The inventors found that when the aldehyde group is excessive after oxidation, it will not only affect the gel effect of the hydrogel, but also have potential cytotoxicity when used as a wound dressing. At the same time, the mechanical properties of the hydrogel are poor, so the key to the success of the present invention is to control the molar ratio of pseudo-Physalis polysaccharide to sodium periodate and the mass ratio of oxidized pseudo-Physalis polysaccharide to carboxymethyl chitosan, so as to finally obtain a pseudo-Physalis polysaccharide hydrogel dressing with excellent mechanical properties, stable structure, fast gelation time, and no cytotoxicity.
[0017] Furthermore, in step (1), the seeds of Physalis alkekengi are heated in a drying oven at 95° C. for 90 minutes to inactivate naturally occurring pectin decomposing enzymes.
[0018] Furthermore, the material-liquid ratio of the deionized water used for soaking and swelling in step (1) is 1:15 (w / v, g / ml).
[0019] Furthermore, the stirring filtration in step (1) is carried out by stirring at 600r for 5 minutes.
[0020] Furthermore, the rotary evaporation in step (1) is performed at 70° C. to reduce the volume to 1 / 4 of the original volume.
[0021] Furthermore, the concentration of ethanol in step (1) is 95% v / v, and the amount of ethanol used is three times the volume of the solution.
[0022] Furthermore, the reaction mixture described in step (2) is placed in a dialysis bag and dialyzed for 3 days, with the water being changed 4 times a day.
[0023] Furthermore, the pre-freezing time in step (2) is 1 hour.
[0024] The second object of the present invention is to provide the oxidized Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel prepared by the above method.
[0025] The third object of the present invention is to provide the use of the oxidized Physalis alkekengi polysaccharide-carboxymethyl chitosan composite hydrogel in the preparation of wound dressings.
[0026] The beneficial effects of the present invention are as follows:
[0027] The present invention provides an injectable, self-healing oxidized Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel and a preparation method and application thereof, which has the following advantages:
[0028] (1) The present invention can prepare a hydrogel with good performance by using only two raw materials, Physalis sylvestris polysaccharide and carboxymethyl chitosan, which is economically reasonable.
[0029] (2) The hydrogel of the present invention is semi-solid, has solid elastic characteristics, good adhesion, and can fit tightly to the wound surface.
[0030] (3) The hydrogel of the present invention has strong water retention properties and can create and maintain a moist environment, providing an ideal environment for wound healing.
[0031] (4) The present invention adopts dynamic reversible covalent cross-linking to prepare the composite hydrogel, and the preparation steps are simplified. The composite hydrogel is prepared by simple mixing under certain solution conditions, thus avoiding the use of toxic cross-linking agents. The preparation process is safe and easy to operate.
[0032] (5) The Physalis sylvestris polysaccharide and carboxymethyl chitosan used in the present invention are derived from plants and animals, respectively. Compared with synthetic polymers, they are easy to obtain and have high safety.
[0033] (6) The composite hydrogel prepared by the present invention has a gel time of 5 to 10 seconds, which can meet the need for rapid hemostasis of wounds.
[0034] (7) After screening, the final oxidized Physalis sylvestris polysaccharide content of the hydrogel prepared by the present invention was 0.5%, and the carboxymethyl chitosan content was 1%. The low content of polysaccharide can prepare a hydrogel with stable performance, which helps to save preparation costs.
[0035] (8) In the hydrogel prepared by the present invention, the mass ratio of oxidized Physalis polysaccharide to carboxymethyl chitosan is 1:2. Too high an aldehyde concentration not only affects the gelling effect of the hydrogel, but also has potential cytotoxicity when used as a wound dressing. Therefore, a suitable ratio of amino groups to aldehyde groups is the key to the successful preparation of the composite hydrogel. BRIEF DESCRIPTION OF THE DRAWINGS
[0036] Figure 1 This is a process flow chart for preparing oxidized Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel;
[0037] Figure 2 For NaIO 4 Effect of dosage on the aldehyde content of Physalis chinensis polysaccharides;
[0038] Figure 3 Schematic diagram for gel effect screening;
[0039] Figure 4 Schematic diagram of the gelation of oxidized Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel;
[0040] Figure 5 This is the cross-linking mechanism diagram of oxidized Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel;
[0041] Figure 6 FTIR images of composite hydrogel H20 and polysaccharides CMC, ONPGP 20%, and NPGP;
[0042] Figure 7 20% for NPGP and ONPGP H-1 NMR spectra;
[0043] Figure 8 XRD patterns of CMC, NPGP and hydrogels H0, H20, H40, and H60;
[0044] Fig. 9 TG graphs of CMC, NPGP and hydrogels H0, H20, H40, and H60;
[0045] Fig.10 Swelling rate (A) and degradation rate (B) of hydrogels H0, H20, H40, and H60 in PBS;
[0046] Fig.11 Compression diagrams of hydrogels H0, H20, H40, and H60;
[0047] Fig.12 are the shear rate diagrams of hydrogels H0, H20, H40, and H60;
[0048] Fig.13 The results of hydrogel rheological tests and the macroscopic self-healing effect diagram;
[0049] Fig.14 Schematic diagram of the injectability of H20 hydrogel;
[0050] Fig.15 This is the adhesion effect diagram of H20 hydrogel to skin;
[0051] Fig.16 This is the cell viability result graph of L929 cells incubated with H0 and H20 hydrogels on the third day. DETAILED DESCRIPTION
[0052] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described in detail below in conjunction with the embodiments. It is necessary to point out that the following embodiments are only used to explain and illustrate the present invention and are not used to limit the present invention. Some non-essential improvements and adjustments made by those skilled in the art based on the above invention content still belong to the protection scope of the present invention.
[0053] Example 1
[0054] (I) Preparation of composite hydrogel
[0055] The process flow chart of preparing Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel is as follows Figure 1 As shown, it mainly includes the following steps:
[0056] (1) Extraction of Physalis polysaccharides: Heat the seeds of Physalis in a drying oven at 95°C for 90 minutes to inactivate the naturally occurring pectin degrading enzymes. Soak the dried seeds in deionized water at a solid-liquid ratio of 1:15 (w / v, g / ml) overnight to fully swell them. Stir in a blender at 600r for 5 minutes. Collect the solution through a fine-mesh nylon gauze filter and rotary evaporate the solution (70°C) until it reaches 1 / 4 of the original volume, then add three times the volume of 95% ethanol (v / v) to precipitate the polysaccharides at 4°C overnight. Collect the polysaccharide precipitate, dissolve it in distilled water, and then rotary evaporate the residual ethanol. Freeze-dry to obtain Physalis polysaccharides;
[0057] (2) Oxidation of Physalis polysaccharide: Weigh 5 g of Physalis polysaccharide and add it to 600 mL of deionized water. Stir at 55°C to fully dissolve it. Weigh 0%, 20%, 40%, 60%, 80%, and 100% of sodium periodate in molar amounts of Physalis polysaccharide and dissolve it in water. Add it to the Physalis polysaccharide aqueous solution under light-proof conditions. React at room temperature in the dark for 0.5 h. Add an equal molar amount of ethylene glycol to sodium periodate and continue stirring for 30 min to terminate the reaction. The reaction mixture was placed in a dialysis bag and dialyzed for 3 days, with the water changed 4 times a day. After the dialysis, the product was pre-frozen in a refrigerator and then freeze-dried in a vacuum freeze dryer to obtain oxidized Physalis polysaccharides with different aldehyde content. The oxidized Physalis polysaccharides obtained by oxidation with different amounts of sodium periodate were named: NPGP, ONPGP20%, ONPGP 40%, ONPGP 60%, ONPGP 80%, and ONPGP 100%;
[0058] (3) Determination of the aldehyde content of oxidized Physalis polysaccharides: Accurately weigh 8.69 g of hydroxylamine hydrochloride dried to constant weight and add it to 75 mL of deionized water. After stirring evenly, add 3 mL of 0.05% methyl orange aqueous solution, mix evenly, and dilute to 500 mL with deionized water to obtain a 0.25 mol / L hydroxylamine hydrochloride-methyl orange solution. Weigh 0.10 g of oxidized Physalis polysaccharides dried to constant weight and add them to 25 mL of 0.25 mol / L hydroxylamine hydrochloride-methyl orange solution, and stir thoroughly to dissolve them into a uniform solution. Using 0.1 mol / L standard NaOH aqueous solution as the titrant, the amount of HCl released in the solution was determined by potentiometric titration. Finally, the aldehyde content and degree of oxidation of Physalis polysaccharides oxidized with different amounts of sodium periodate were calculated based on the amount of NaOH consumed. The results are as follows: Figure 2 As shown: When sodium periodate is used as an oxidant to oxidize Physalis polysaccharide, as the amount of sodium periodate increases, the aldehyde content in the structure of Physalis polysaccharide increases. In the structure of Physalis polysaccharide that has not been oxidized, the aldehyde content is zero. When the amount of sodium periodate reaches 60%, the aldehyde content in the structure of Physalis polysaccharide reaches the maximum value, and as the amount of sodium periodate increases, the aldehyde content in the structure of Physalis polysaccharide does not change significantly. However, when the amount of sodium periodate is too much, the molecular weight of the polysaccharide will be broken, and the water solubility and viscosity will decrease. Therefore, NPGP, ONPGP 20%, ONPGP 40%, and ONPGP 60% were selected to prepare composite hydrogels with carboxymethyl chitosan respectively; the results are shown in Figure 2 shown.
[0059] (4) Preparing an oxidized Physalis polysaccharide solution: weighing 1 g of oxidized Physalis polysaccharide and dissolving it in 100 mL of deionized water to prepare an oxidized Physalis polysaccharide solution;
[0060] (5) preparing carboxymethyl chitosan solution: weighing carboxymethyl chitosan and dissolving it in deionized water to prepare carboxymethyl chitosan solutions with different mass fractions: 0.5%, 1%, 2%, 3%, and 4%;
[0061] (6) Preparation of oxidized Pseudo-Physalis polysaccharide-carboxymethyl chitosan composite hydrogel: Prepare oxidized Pseudo-Physalis polysaccharide solutions with different aldehyde contents, NPGP, ONPGP 20%, ONPGP 40%, ONPGP 60%, according to step (4); prepare carboxymethyl chitosan solution according to step (5). The oxidized Pseudo-Physalis polysaccharide solutions with different aldehyde contents were mixed with the carboxymethyl chitosan solution at a volume ratio of 1:1 (v / v) at room temperature, and vortexed in a vortexer for 10 seconds to obtain oxidized Pseudo-Physalis polysaccharide-carboxymethyl chitosan composite hydrogel. The gel effect is as follows: Figure 3 shown.
[0062] (7) According to Figure 3Based on the results, 1% NPGP, 20% ONPGP, 40% ONPGP, and 60% ONPGP aqueous solutions were selected and mixed with 2% CMC aqueous solution at a volume ratio of 1:1 to prepare composite hydrogels, which were named H0, H20, H40, and H60, respectively, and a series of characterizations were performed. The gelation schematic diagram and cross-linking mechanism diagram of the hydrogel are shown in Figure 2. Figure 4 and Figure 5 shown.
[0063] (II) Structural characterization of hydrogels
[0064] 1. Fourier transform infrared spectroscopy
[0065] Oxidized Physalis sylvestris polysaccharides NPGP, ONPGP 20%, ONPGP 40%, ONPGP 60% and hydrogels H0, H20, H40, H60 with different aldehyde contents were freeze-dried, mixed with KBr at a mass ratio of 1:200, ground evenly, pressed into thin sheets, and then observed at a wavelength of 400-4000 cm -1 The result is as follows: Figure 6 Shown: 3430cm -1 The stretching vibration of HO and NH of carboxymethyl chitosan is at 2940 cm -1 Representative sugars -CH 2 or -CH 3 -CH stretching vibration; 1743cm -1 It is the stretching vibration of aldehyde C=O; 1017cm -1 、1104cm -1 The characteristic absorption peak of pyranose is at 1623cm -1 It is the stretching vibration of the C=N in the amide bond.
[0066] The FT-IR spectra of ONPGP 20% and NPGP are very similar, which may be due to the formation of hemiacetal, resulting in weaker signals for the aldehyde group. However, ONPGP 20% has a strong signal at 1017 cm -1 、1104cm -1 The characteristic peak of pyranose disappeared, indicating that the structure of Pseudo-Physalis polysaccharide changed after sodium periodate oxidation. -1 The characteristic peak of aldehyde group at 1623cm -1 The significant enhancement of the characteristic peak of amide bonds at the position jointly verified the successful oxidation of Physalis polysaccharide and the successful preparation of dynamic covalent cross-linked hydrogel based on aldehyde and amino groups.
[0067] 2. Nuclear magnetic resonance hydrogen spectrum determination
[0068] conduct H-1 When NMR testing, deuterated water (D2 O) As a deuterated reagent, 5 mg NPGP / ONPGP 20% was dissolved in 600 μL D 2 O. NPGP and ONPGP 20% H-1 NMR spectra Figure 7 As shown, a new peak at 4.9-5.0 ppm was observed in the spectrum of ONPGP 20%, which corresponded to the hemiacetal protons generated from the aldehyde group and the adjacent hydroxyl group, indicating that the oxidation of Physalis sylvestris polysaccharide was successful.
[0069] 3. X-ray diffraction measurement
[0070] The freeze-dried CMC, NPGP and gel samples were analyzed for their crystalline / amorphous structures in an X-ray diffractometer with a CuKα radiation source of 40 kV and an operating wavelength of like Figure 8 As shown, all hydrogel samples have the same profile, indicating that they are amorphous materials; the diffraction peak of NPGP at 2θ is 21.26°. After being made into hydrogel, the diffraction peak angle is not significantly affected by the aldehyde content, and the diffraction peak intensity increases slightly. The results show that NPGP aldehyde addition enhances the crystallinity of the gel. Combined with the change in the CMC peak, this may be due to the change in the intermolecular interaction between the aldehyde-modified NPGP and the amino groups in CMC through the Schiff base reaction. This is consistent with the FTIR and H-1 The results of NMR were consistent.
[0071] 4. Thermogravimetric determination:
[0072] In the temperature range of 20~900℃, the speed is 20℃ / min. -1 The effect of the aldehyde content of Physalis polysaccharide on the thermal stability of Physalis polysaccharide-carboxymethyl chitosan composite hydrogel was investigated by thermogravimetric analysis under nitrogen atmosphere. Fig. 9 As shown in Figure 2, the weight loss of all samples can be divided into two stages. The first stage is caused by water evaporation, proving that the hydrogel is hydrophilic; the weight loss of the second stage is attributed to the scission of the polysaccharide chain.
[0073] (III) Determination of the physical and chemical properties of hydrogels
[0074] 1. Swelling and degradation test
[0075] Place the freeze-dried hydrogel in a 30ml sample bottle, add 20ml PBS (pH 7.4) to the sample bottle and soak it at room temperature. At regular intervals, use a syringe to remove the PBS in the sample bottle, and use filter paper to absorb the water on the bottle wall and the surface of the hydrogel, and weigh it as W2. Continue to add the same volume of PBS, then weigh and record the weight until the weight of the hydrogel no longer increases; the mass of the hydrogel before soaking is recorded as W1, and the swelling curve is drawn. Place the hydrogel that has reached swelling equilibrium in PBS and soak it at room temperature. Take out the water in the sample bottle at fixed intervals, and use filter paper to wipe the water on the bottle wall and the surface of the hydrogel, and weigh it as W3 until the hydrogel is completely dissolved, and draw the degradation curve of the hydrogel. The calculation formulas for swelling rate and degradation rate are as follows:
[0076]
[0077] like Fig.10 As shown in Figure A, H20, H40, and H60 hydrogels reached swelling equilibrium after being immersed in PBS for 6 hours at room temperature, and the swelling rates were 3168±105%, 3277±106%, and 3304±127%, respectively, with no significant difference. However, H0 hydrogel rapidly degraded after being immersed in PBS for 0.5 hours, with a short stability time and a swelling rate of only 2224±52%, which was significantly lower than that of H20, H40, and H60 hydrogels. This is because after oxidation, the structure of Physalis polysaccharide contains aldehyde groups, which can react with the amino groups contained in the carboxymethyl chitosan structure through Schiff base to produce covalent crosslinks, thereby increasing the structural stability of the hydrogel network. When the hydrogels continued to be immersed after reaching swelling equilibrium, H0 hydrogel began to degrade rapidly after being immersed for 0.5 hours and completed degradation within 4 hours; H20, H40, and H60 hydrogels began to degrade after being immersed for 8 hours and degraded completely within 84 hours. The results are shown in the figure below. Fig.10 B. The results show that the hydrogel covalently cross-linked based on Schiff base reaction has a high swelling rate, has the potential to absorb tissue wound exudate, and has a certain biodegradability.
[0078] 2. Compression test
[0079] Prepare the hydrogel sample, balance it in a constant temperature oscillator at 200r for 4h at room temperature, and then test the compressive strength on a universal testing machine. Before the experiment, use an electronic vernier caliper to measure the height of the hydrogel to be 10mm and the diameter to be 15mm. Set the sensor weight to 5000gf, the compression speed of the sample to 3mm / min, and use the fracture stress as the detection index. Fig.11The strain stress strain curves of four types of hydrogels are shown. The rupture strains of H0, H20, H40, and H60 are 2.3KPa, 23KPa, 10KPa, and 6.5KPa, respectively. As can be seen from the figure, after the aldehyde-forming of the Physalis polysaccharide, covalent cross-linking with the amino groups in the carboxymethyl chitosan structure can significantly improve the mechanical properties of the hydrogel and increase the compressive strength. However, excessive oxidation will cause the molecular weight of the polysaccharide to break and the viscosity to decrease, thereby reducing the mechanical properties of the hydrogel.
[0080] 3. Rheological properties test
[0081] The fluid properties and self-healing of the hydrogels were measured using a rheometer at 37°C. The test rotor was PP50, the temperature was 37°C, and the gap distance was set to 1 mm.
[0082] (1) Steady-state rheological test
[0083] Set the shear rate range to 0.1 to 100 s -1 The apparent viscosity of the sample is a function of the shear rate, and the data is analyzed using the Power-law model. Fig.12 As shown in the figure, the apparent viscosity of all groups of hydrogels decreases with increasing shear rate, indicating that these gels have shear thinning properties in nature; sodium periodate oxidizes the Pseudo-Physalis polysaccharide, which can enhance the shear thinning properties of the gel. The apparent viscosity of the gel with an oxidant addition of 20% is the highest, because with the increase in the amount of oxidant added, not only can the vicinal diol be selectively oxidized to aldehyde groups, but also the polysaccharide molecular chain can be broken, the molecular weight can be reduced, and side reactions can be induced. The apparent viscosity curve of the hydrogel is fitted to the power law model through the power law equation to obtain the power law parameters of the hydrogels with different aldehyde content. The results are shown in Table 1. The n values of all samples are less than 1, indicating that the hydrogel is a pseudoplastic fluid; with the increase of aldehyde content, the k value decreases, and n decreases, which means that with the increase of aldehyde content, the pseudoplasticity of the gel decreases. The above results show that the introduction of aldehyde groups plays a key role in improving the fluid properties of Pseudo-Physalis polysaccharide-carboxymethyl chitosan composite hydrogel.
[0084] Power law equation: η=K(γ)n
[0085] Where: η is the apparent viscosity; K is the viscosity index (Pa·s n ); γ is the shear rate (s -1 ); n is the shear rate dependence index (power law index)
[0086] Table 1 Hydrogel power law fitting parameters
[0087]
[0088] (2) Dynamic rheological test
[0089] The hydrogel was subjected to shear strain scanning by dynamic oscillation, with the test range of 10% to 1000% and the frequency of 1 Hz. Dynamic frequency scanning was performed within the scanning range of 10 to 100 rad / s, and the storage modulus (G′) and loss modulus (G″) of the hydrogel were recorded. The H20 hydrogel was subjected to time alternating scanning at 1000% strain and 1% strain to observe the self-healing effect of the hydrogel, with the alternating time of 90 s, the normal force of 0.1 N and the frequency of 1 Hz. The results are as follows: Fig.13 shown. Fig.13 The G′ curve and G″ curve of all hydrogels in A intersect, and the decrease of G′ value and the increase of G″ value near the intersection point indicate the collapse of the hydrogel structure, indicating that the hydrogel has a transition diagram from a solid with gel properties to a liquid-like with fluid properties. Fig.13 For all hydrogels in B, G′>G″, and both G′ and G″ showed good frequency stability, indicating good cross-linking. The self-healing properties of the hydrogels are shown in Figure 2. Fig.13 As shown in Figure C, under high strains of 1% to 1000%, G″>G′, and the structure of the hydrogel collapsed; after the high strain was removed, G′ and G″ both returned to the initial value (G′>G″), and the hydrogel network recovered autonomously; the viscoelastic phase transition was repeated for at least 7 cycles, with high and low pressures applied every 15 seconds, and the hydrogel network collapsed and recovered regularly, showing rapid and effective self-healing ability. This is mainly the result of the dynamic reversible imine bond. In addition, the H20 hydrogel was cut in half, generally stained with methylene blue, and then the two halves of the hydrogel were put together. The results showed that the methylene blue-stained semicircular hydrogel and the unstained semicircular hydrogel could heal into a circular hydrogel after standing for one night. The joints of the hydrogel had completely self-healed and there were no cracks. From a macroscopic perspective, it can be seen that the H20 hydrogel has excellent self-healing properties, such as Fig.13 As shown in D.
[0090] 4. Injectability test
[0091] The H20 hydrogel was injected into PBS with a syringe. The hydrogel had good integrity in PBS. This indicates that the H20 hydrogel has good injectability and has the potential to be injected in situ into the wound. Fig.14 shown.
[0092] 5. Adhesion test
[0093] The prepared H20 hydrogel was cut into strips of 2.5 cm in length and 1 cm in width and attached to the index finger. The strips were bent 90° or inverted, but the hydrogel did not fall off, indicating that the hydrogel had excellent adhesion to the skin and had the potential to be used as a wound dressing. The results were as follows Fig.15 shown.
[0094] 6. Cytotoxicity test
[0095] (1) The freeze-dried H0 and H20 hydrogels were sterilized by ultraviolet irradiation for 30 min, and 0.001, 0.002, 0.004, and 0.006 g of the sterilized hydrogels were weighed and washed repeatedly with DMEM culture medium (containing 10% fetal bovine serum and 1% penicillin-streptomycin), and then placed in 2 mL of DMEM culture medium to make 0.5, 1, 2, and 3 mg / ml, soaked at 37°C for 24 h, and filtered with a 0.22 μm cellulose acetate filter membrane to prepare sample solutions for later use.
[0096] (2) In a 96-well plate, a concentration of 1.0 × 10 5 Mouse fibroblasts (L929) were dispersed in 100 μL DMEM medium, and freshly prepared sample solution was added. The cells were incubated at 37°C and 5% CO 2 After incubation for 3 days under atmosphere, CCK-8 solution (10 μL) was added to the well plate and cultured for 24 h. The absorbance of the sample at 450 nm was measured with an ELISA instrument, and the relative cell viability was calculated. The cell viability calculation formula is as follows:
[0097]
[0098] in:
[0099] OD S is the absorbance of the sample group (including cells, CCK-8 and sample solution),
[0100] ODb is the absorbance of the blank group (containing DMEM medium and CCK-8 solution), and ODn is the absorbance of the negative control group (containing cells, CCK-8 solution and DMEM medium).
[0101] Cytotoxicity test results Fig.16 As shown, compared with the control group, the cell viability of H0 and H20 hydrogels with different concentrations after incubation with L929 cells for three days was as high as 95% or more, and there was no significant difference compared with the control group. This shows that the prepared hydrogel has no potential cytotoxicity and has the potential to be used for wound dressings.
Claims
1. A method for preparing an oxidized Physalis sylvestris polysaccharide-carboxymethyl chitosan composite hydrogel, characterized in that: The following steps are involved: (1) Extraction of Physalis polysaccharide: Dry the seeds of Physalis to obtain dry seeds, soak them in deionized water to swell them, stir and filter to collect the solution, perform rotary evaporation, then add ethanol to precipitate polysaccharides at 4°C, collect the polysaccharide precipitate, and freeze-dry to obtain Physalis polysaccharide; (2) Oxidation of Physalis polysaccharide: dissolve Physalis polysaccharide in water, stir at 55°C to fully dissolve it, and then mix it with sodium periodate, wherein the molar ratio of the Physalis polysaccharide to sodium periodate is 5:1, and react at room temperature in the dark for 0.5 h. Add ethylene glycol in an amount equivalent to sodium periodate and continue stirring for 30 min to terminate the reaction. The reaction mixture is dialyzed. After the dialysis is completed, the obtained product is pre-frozen and then freeze-dried in a vacuum freeze dryer to obtain oxidized Physalis polysaccharide, which is prepared into a solution. (3) preparing a carboxymethyl chitosan solution: weighing carboxymethyl chitosan and dissolving it in deionized water to prepare a carboxymethyl chitosan solution with a concentration of 1 wt %; (4) Preparation of oxidized Physalis polysaccharide-carboxymethyl chitosan composite hydrogel: oxidized Physalis polysaccharide solution and carboxymethyl chitosan solution were mixed in a mass ratio of 1:2, and vortexed in a vortexer for 10 seconds to obtain oxidized Physalis polysaccharide-carboxymethyl chitosan composite hydrogel.
2. The method according to claim 1, characterized in that In step (1), the seeds of Physalis alkekengi are heated in a drying oven at 95° C. for 90 minutes to inactivate naturally occurring pectin decomposing enzymes.
3. The method according to claim 1, characterized in that The material-liquid ratio for soaking and swelling with deionized water in step (1) is 1 g:15 ml.
4. The method according to claim 1, characterized in that The stirring filtration in step (1) is stirring at 600r for 5min.
5. The method according to claim 1, characterized in that The rotary evaporation in step (1) is carried out at 70° C. to reduce the volume to 1 / 4 of the original volume.
6. The method according to claim 1, characterized in that The concentration of ethanol in step (1) is 95% v / v, and the amount of ethanol used is three times the volume of the solution.
7. The method according to claim 1, characterized in that The reaction mixture as described in step (2) was placed in a dialysis bag and dialyzed for 3 days, with the water being changed 4 times a day.
8. The method according to claim 1, characterized in that The pre-freezing time in step (2) is 1 hour.
9. The composite hydrogel of Physalis oxidis polysaccharide-carboxymethyl chitosan prepared by the method of claims 1-8.
10. Use of the oxidized Physalis alkekengi polysaccharide-carboxymethyl chitosan composite hydrogel according to claim 9 in the preparation of wound dressings.
Citation Information
Patent Citations
A method for preparing pseudo-sour syrup gum microspheres
CN110721163B